Penetrating Cardiac Injuries: Role of Emergency Thoracotomy - Ihssan Ali Hais Elamery; Maysa Edan Kadim (Diyala Journal of Medicine, 2019)
Background: Due to the increase in violence in recent years due to the wars and the increasing use of weapons and sharp machines such as knives and others, the number of victims of cardiac injuries, especially gunshot wounds, stabbing injuries and other acute machines has increased due to the seriousness of these injuries and complications resulting therefrom.